Effect of Pressure on the Synthesis of Compound Ba0.7Ca0.3TiO3 on the Dielectric Constant - Windarjoto, Windarjoto; Poniman, S; Hadinata, Made Hendra (BULETIN FISIKA, 2020)
Piezoelectric and ferroelectric ceramic materials are widely used for advanced technology. Barium Titanat is one of the ferroelectric materials that are still widely studied today. In this research, Ba 0,7 Ca 0,3 TiO 3 was synthesized. The compound was synthesized by the solid reaction method with variations in pressure during the sample compacting process include 10, 20, and 30 kN. Samples in the form of solids (pellets) were calcined at 800 °C and sintered at 1000 °C for 4 hours respectively. The synthesized product was characterized by an LCR meter. The characterization results in the frequency range of 100-200000 Hz show that the pressure affects of the parameters value of the dielectric constant, especially at frequencies 100-10000 Hz. In that frequency range the dielectric constant decreases very sharply, then above 100 kHz the dielectric constant is almost unchanged with increasing frequency.